Fundamentals of Entrepreneurship ENT 300 : VMac Drink / Timothy Andin ... [et al.] - Andin, Timothy; Embu, Patricia; Kudang, Christina; Abdul Hashim, Nurfarahanim; Abdul Rahman, Nur Ain (2016)
The business plan of vending machine is proposed so that it can be taken by comprehensive manner. This business plan gives us opportunity to assess on business industry in the future. We agreed to form partnership business in order to meet our opportunity in customer services (vending machine). The business is in form of enterprise consisting five shareholders. All shareholders had agreed as stated in the agreement letter that mentioned about the capital, contribution, loss and profit of the business. We choose this business because it shows the equality and no one will be discriminated as the profit or losses are equally divided as stated ratio and the financial manager will announce whether the business is going to gain profit or incur loss by the end of the year-. The partnership is an excellent option for us to take part in because we can share our ideas and knowledge to expand the business, to gain more profit, achieve high productivity from time to time and give a good services to customer.